The synthesis of enantiopure 1,3-dimethylisochroman and related racemic analogues using anacardic Acid as a bio-renewable starting material - Lu, Tianqi (My University, 2019)
Isochromans are a class of oxygenated heterocycles with a 3,4-dihydro-1H-benzo[c]pyran scaffold that are found in a variety of natural sources including bacteria, fungal, plants and insects. Isochroman-containing compounds display a wide range of biological activities including anti-bacterial, anti-tumour, anti-oxidation, anti-hypertension and herbicidal activities. The dissertation involves research evaluating the use of lipase from Candida rugosa for the enzymatic kinetic resolution of an advanced synthetic intermediate rac-1-(2-allyl-3,6-dimethoxyphenyl)ethanol which eventually resulted in the enantiopure synthesis of (S)-5,8-dimethoxy-1,3-dimethylisochroman. The synthesis of (S)-5,8-dimethoxy-1,3-dimethylisochroman commenced with the diallylation of 2,5-dihydroxybenzoic acid. The allylated compound allyl 5-(allyloxy)-2-hydroxybenzoate was then subjected to a thermal Claisen-rearrangement to afford allyl 2-allyl-3,6-dihydroxybenzoate which was then protected using dimethylsulphate. The dimethoxy compound allyl 2-allyl-3,6-dimethoxybenzoate was reduced to form alcohol (2-allyl-3,6-dimethoxyphenyl) methanol using lithium aluminium hydride followed by a PCC oxidation yielding aldehyde 2-allyl-3,6-dimethoxybenzaldehyde. The aldehyde was then treated with freshly made methylmagnesium iodide to yield the alcohol 1-(2-allyl-3,6-dimethoxyphenyl)ethanol as the racemate which was then acetylated to form rac-1-(2-allyl-3,6-dimethoxyphenyl)ethyl acetate. Using lipase hydrolysis of the acetate racemate, we were able to obtain enantiopure (S)-1-(2-allyl-3,6-dimethoxyphenyl)ethanol which was then followed by potassium tert-butoxide ring closure to afford (S)-5,8-dimethoxy-1,3-dimethylisochroman with an overall yield of 1.31% starting from 2,5-dihydroxybenzoic acid. In this dissertation, we also demonstrated the synthesis of hydroquinone methyl 3-bromo-2,5-dihydroxy-6-pentadecylbenzoate using the bio-renewable substrate anacardic acid as starting material. Starting with the selective methylation of anacardic acid possessing a saturated side chain, methyl 2-hydroxy-6-pentadecyl benzoate was synthesized which was subjected to N-bromosuccinimide bromination to afford methyl 3,5-dibromo-2-hydroxy-6-pentadecyl benzoate. A Ceric(IV) ammonium nitrate oxidation followed by sodium dithionite reduction afforded methyl 3-bromo-2,5-dihydroxy-6-pentadecylbenzoate in an overall yield of 31% from anacardic acid. Using anacardic acid as starting material and potassium tert-butoxide as a key step for the ring closure, we were able to synthesize another two isochroman; rac-8-methoxy-1,3-dimethylisochroman was synthesized over 9 steps with an overall yield of 13% and rac-8-methoxy-1-methyl-3-tridecylisochroman was synthesized over 7 steps with an overall yield of 16%.
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg In fulfilment of the requirements for the Degree of Master of Science October 2019
Keywords: Enantiomers; Enantiomers--Analysis